2020
DOI: 10.1021/acsabm.0c00015
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic, Tissue-Adhesive Colloidal Wound Dressing Functionalized by UV Irradiation

Abstract: Topical hemostatic agents have been widely used to stop intra-/postoperative bleeding from wounds and resected tissue surfaces. However, hemostatic agents that can accelerate blood coagulation and promote wound healing have not been established because of their poor tissue adhesiveness under wet conditions. Here, we report a colloidal wound dressing of hemostatic and tissue-adhesive hydrophobized microparticles (hMPs) functionalized by UV irradiation. hMPs were prepared by adding ethanol to hydrophobically mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The masses of MnO 2 used in the mouse tail amputation model (2.3 mg) and the mouse hepatic hemorrhage model (2.8 mg) were slightly higher than that of MnO 2 @PDA but with no significant difference. The results indicate that the desirable hemostatic effect of MnO 2 @PDA is attributed to its PDA modification, which may be beneficial in promoting wound healing and reducing the probability of adhesion . The hemostatic performance of MnO 2 @PDA and a commercial chitosan hemostatic powder (Biotemed) was also compared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The masses of MnO 2 used in the mouse tail amputation model (2.3 mg) and the mouse hepatic hemorrhage model (2.8 mg) were slightly higher than that of MnO 2 @PDA but with no significant difference. The results indicate that the desirable hemostatic effect of MnO 2 @PDA is attributed to its PDA modification, which may be beneficial in promoting wound healing and reducing the probability of adhesion . The hemostatic performance of MnO 2 @PDA and a commercial chitosan hemostatic powder (Biotemed) was also compared.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate that the desirable hemostatic effect of MnO 2 @ PDA is attributed to its PDA modification, which may be beneficial in promoting wound healing and reducing the probability of adhesion. 38 The hemostatic performance of MnO 2 @PDA and a commercial chitosan hemostatic powder (Biotemed) was also compared. As shown in Figure S8, MnO 2 @PDA possessed a hemostasis ability comparable to that of the commercial hemostatic powder.…”
Section: Tissue Adhesiveness Of Mno 2 @Pdamentioning
confidence: 99%
“…In addition to the physical forces mentioned above, there are some forces, such as hydrophobic forces, which anchor the material to the tissue to enhance adhesion. Taguchi’s group also reported that the materials enhanced the tissue adhesion by anchoring the hydrophobic part on the ECM, and the adhesion strength depended on the molecular hydrophobicity …”
Section: Adhesion Mechanisms Of Hydrogel-based Wound Dressingsmentioning
confidence: 99%
“…Taguchi's group also reported that the materials enhanced the tissue adhesion by anchoring the hydrophobic part on the ECM, and the adhesion strength depended on the molecular hydrophobicity. 77 Focusing on the mechanical aspects of bonding, various toughening mechanisms have been implemented in hydrogels to enhance fracture energy, 78 but the potential of hightoughness hydrogels as adhesive implants has not been well explored. Karami et al developed a hydrogel with strong adhesion to soft tissues such as articular cartilage and meniscus.…”
Section: T H Imentioning
confidence: 99%
“…In order to solve the problem of weak adhesion in wet dynamic environment, a tissue‐adhesive based on hydrophobized microparticles (hMPs) was fabricated through addition of ethanol to the solution of hydrophobically‐modified Alaska pollock gelatin using a coacervation method. [ 78 ] Moreover, various hydrophilic functional groups can be introduced on its surface through UV irradiation to improve the swelling performance of hMPs in blood. The experimental results showed that hMPs retained tissue adhesion following UV irradiation, due to the strong cohesion caused by the hydrophobic interactions between hMPs.…”
Section: Introductionmentioning
confidence: 99%